Studies of the Change in the Time Constants of the Discharge of the Capacitor to Predict the Residual life of the Operation of the Electric Motor - 10.52254/1857-0070.2023.3-59.13; Matviienko A. (Problems of the Regional Energetics, 2023)
Forecasting the resource of the electric motor makes it possible to increase the reliability of the operation of the electrical complex. The aim of the work is to study the possibility of using changes in the capacitor discharge time constants under conditions of local reactive power compensation as a criterion parameter for predicting the life of an electric motor. To achieve this goal, the following tasks were solved: an analysis of methods for predicting the resource of an electric motor was carried out, a differential equation was analyzed, and relationships between the insulation resistance and the capacitor discharge time constants were established. The most important result is the establishment of the relationship between the state of the insulation and the value of the time constant of the discharge of the capacitor. The most significant result is that the change in the time constant of the discharge is used as a criterion parameter for predicting the resource of the electric motor. The significance of the study is that the value obtained after the first shutdown of the electric motor is taken as the base value of the discharge time constant. The limiting values of the discharge time constants make it possible to estimate the resource of the electric motor after each shutdown. A method and a device for monitoring open-phase network modes are proposed, and when disconnected, control the value of the insulation resistance of the electric motor and predict the residual life of the electric motor.